EU rescue and restructuring state aid guidelines : an opportunity to restructure corporate governance and corporate culture - Obradović Mazal, Tamara (Array, 2019)
Undertakings in difficulty, having exhausted all market options, may resort to State aid to rescue and/or restructure its operations in order to return to viability. the author looks closer into the opportunity for such undertakings to change within so as to abandon practices which may have represented at least one of the roots of the deficiencies leading them to difficulties. The stringent rules of rescue and restructuring of firms in difficulties provide a second chance to restore their business, account of debts, take stock of actions and potentially rise again. Yet, the overall restructuring given as a second chance by the State aid and the role of the state, should not present a carte blanche for old policies and approaches to be repeated with the taxpayers’ money. The restructuring should also be a stock-taking opportunity, an internal scrutiny where the corporate culture and the governance of the undertaking changes as well. There should be room to (re)consider corporate governance and audit of corporate culture as elements of restructuring process as well as restructuring plans, to prevent the undertaking on the receiving end of State aid to lapse again. Being given a second chance, applying practices and exercising behaviour that (may) have lead the undertaking to its difficulties, is not a guarantee of successful restructuring and return to viability but may, indeed, represent an internal subjective peril to the objective restructuring goals to be achieved. Hence, the author explores whether non-tangible elements such as an enhanced corporate governance and change of corporate culture, should be introduced as mandatory in the course of undertaking restructuring. The author does not probe into corporate governance and corporate culture as such, but perceives them as welcoming factors to achieve the desired outcome of restructuring aid, namely a successful return to viability using restructuring aid.